1992
DOI: 10.1088/0954-3899/18/3/011
|View full text |Cite
|
Sign up to set email alerts
|

The energy dependence of the inelasticity and the nucleonic cascade

Abstract: We obtain a simple solution for the ondimensional nucleonic diffusion equation in the atmosphere assuming both interaction mean free path and inelasticity BS energy dependent. We also show that a fairly accurate description of nucleonic fluxes is obtained by using the average inelasticity bp an inereasing function of energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[9] that the charged multiparticle distributions referred to above imply a smooth decrease of inelasticity with energy. It has been shown that such a behavior of multiparticle production is not compatible with some cosmic-ray data, such as the altitude dependence of the intensity of electromagnetic component [9], the energy spectrum of nucleonic component [14], and recent data from Fly's Eye experiment [15], all of them concerning showers generated by a primary cosmic ray at the top of the atmosphere. However, that question still remains unsolved for the case of single-particle generated events, such as superfamilies.…”
Section: Introductionmentioning
confidence: 99%
“…[9] that the charged multiparticle distributions referred to above imply a smooth decrease of inelasticity with energy. It has been shown that such a behavior of multiparticle production is not compatible with some cosmic-ray data, such as the altitude dependence of the intensity of electromagnetic component [9], the energy spectrum of nucleonic component [14], and recent data from Fly's Eye experiment [15], all of them concerning showers generated by a primary cosmic ray at the top of the atmosphere. However, that question still remains unsolved for the case of single-particle generated events, such as superfamilies.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in Refs. [1,2] that, when one supposes the interaction mean-free-path and the mean elasticity as energy-dependent quantitites, the analytical solution for the nucleonic diffusion equation in the atmosphere is given by…”
mentioning
confidence: 99%
“…In previous papers [1,2,3] we have discussed the importance of the energy dependence of the leading particle spectrum, which was done through the mean inelasticity. As a first approach, we have neglected the diffractive interactions in the proton-air collisions.…”
mentioning
confidence: 99%
“…Applying this method we can reproduce the solutions of Nishimura to eletromagnetic cascades written in the Mellin's space 9]. Analytical solutions in the con guration space have been obtained applying this method to the study of hadronic cascades iniciated on the top of atmosphere by a primary ux with a power-law energy dependence 10,11].…”
Section: Introductionmentioning
confidence: 99%